Comparison of pens without and with multilevel platforms for growing rabbits. Issue 2 (3rd April 2018) - Matics, Zsolt; Farkas, Tamás Péter; Dal Bosco, Alessandro; Szendrő, Zsolt; Filiou, Eirini; Nagy, István; Odermatt, Meinrad; Paci, Gisella; Gerencsér, Zsolt
Abstract: This experiment compared the productive performance and location of growing rabbits in pens without and with two-level platforms (wire-mesh or plastic-mesh). A total of 174 rabbits of both sexes weaned at 5 weeks of age were randomly divided into three groups ( n = 58 rabbits/group, 2 pens/treatment, 29 rabbits/pen). The floor area of pens was 1.0 × 1.83 m, and the floor was made of wire-mesh. Two pens were equipped with wire-mesh (WP) and two pens with plastic-mesh elevated platforms (PP) on two levels, and two pens were without platforms (NoP). Treatment had no effect on the productive performance of growing rabbits. Based on video recordings, animal density (rabbits/m 2 in each location) was higher ( p < .001) on the floor than on the platforms (in WP: 12.0 vs. 5.2, in PP: 10.2 vs. 7.4 rabbits/m 2, respectively). Animal density on the floor was higher ( p < .001) in front of the platforms than under the platforms (in WP 15.7 vs. 9.8 rabbits/m 2 and in PP 13.3 vs. 8.3 rabbits/m 2, respectively). The animal density on platforms was 1.4 times higher in group of PP than in WP (p < .001). The animal density was 1.6 and 2.9 times higher on the second floor than on the first one (p < .001), in group of PP and WP, respectively. The concentration of cortisol metabolites in faeces and the ratio of injured rabbits were similar in the three groups. The rabbits showed higher preference staying on the floor compared to the platform. Pens with platforms were not influencing productive performance.